Long-term low intensity physical exercise attenuates heart failure development in aging spontaneously hypertensive rats - Pagan, Luana Urbano [UNESP]; Damatto, Ricardo Luiz [UNESP]; Cezar, Marcelo Diarcadia Mariano [UNESP]; Lima, Aline Regina Ruiz [UNESP]; Bonomo, Camila [UNESP]; Campos, Dijon Henrique Salomé de [UNESP]; Gomes, Mariana Janini [UNESP]; Martinez, Paula Felippe; Oliveira Junior, Silvio Assis de; Gimenes, Rodrigo [UNESP]; Rosa, Camila Moreno [UNESP]; Guizoni, Daniele Mendes [UNESP]; et al. (Karger, 2015)
Background: Physical exercise is a strategy to control hypertension and attenuate pressure overload-induced cardiac remodeling. The influence of exercise on cardiac remodeling during uncontrolled hypertension is not established. We evaluated the effects of a long-term low intensity aerobic exercise protocol on heart failure (HF) development and cardiac remodeling in aging spontaneously hypertensive rats (SHR). Methods: Sixteen month old SHR (n=50) and normotensive Wistar-Kyoto (WKY, n=35) rats were divided into sedentary (SED) and exercised (EX) groups. Rats exercised in treadmill at 12 m/min, 30 min/day, 5 days/week, for four months. The frequency of HF features was evaluated at euthanasia. Statistical analyses: ANOVA and Tukey or Mann-Whitney, and Goodman test. Results: Despite slightly higher systolic blood pressure, SHR-EX had better functional capacity and lower HF frequency than SHR-SED. Echocardiography and tissue Doppler imaging showed no differences between SHR groups. In SHR-EX, however, left ventricular (LV) systolic diameter, larger in SHR-SED than WKY-SED, and endocardial fractional shortening, lower in SHR-SED than WKY-SED, had values between those in WKY-EX and SHR-SED not differing from either group. Myocardial function, assessed in LV papillary muscles, showed improvement in SHR-EX over SHR-SED and WKY-EX. LV myocardial collagen fraction and type I and III collagen gene expression were increased in SHR groups. Myocardial hydroxyproline concentration was lower in SHR-EX than SHR-SED. Lysyl oxidase gene expression was higher in SHR-SED than WKY-SED. Conclusion: Exercise improves functional capacity and reduces decompensated HF in aging SHR independent of elevated arterial pressure. Improvement in functional status is combined with attenuation of LV and myocardial dysfunction and fibrosis.
Keywords: Spontaneously hypertensive rat; Tissue Doppler imaging; Echocardiography; Papillary muscle; Myocardial fibrosis